Green Innovation in Social Media Discourse: Electrification of Online Motorcycle Taxi and Environmental Economy Implications - Nugroho, Aris Widyo; Prasetyo, Satria Iman; Nyeleker, Kerkulah P (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2025)
This study aims to analyse the discourse of online motorcycle taxi drivers on social media related to transportation electrification and its impacts on the economy and environment in DKI Jakarta. The main focus of this study is to understand the views, experiences, and interactions of online motorcycle taxi drivers who play an essential role in the urban transportation ecosystem. Using a qualitative approach and the Computer-Assisted Qualitative Data Analysis (CAQDAS) method, this study digs deeper into the discussion on social media about transportation electrification. It describes drivers' challenges, desires, and attitudes regarding green innovation. CAQDAS was chosen because of its ability to manage and analyse large volumes of qualitative data, allowing for the systematic identification of themes and patterns of discourse. The results show that adopting green innovation in the transportation sector, especially online motorcycle taxi electrification is influenced by external pressures such as consumer awareness and government policies, as well as collaboration between technology companies and drivers. Sentiment analysis shows the dominance of positive sentiment from optimistic drivers about cost savings and sustainability, although there are still practical barriers, such as initial costs and limited infrastructure. These findings emphasise the importance of proactive policies in supporting the transition to sustainable and environmentally friendly electric vehicles, considering the needs of drivers, companies, and the public sector. This research contributes to the understanding of factors influencing the adoption of electric transportation among online motorcycle taxi drivers and the economic and environmental implications of the transition.